Presidential Address: National Unity and the Politics of Political History - Cuthbert Brandt, Gail (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1992)
AbstractThe latest lengthy round of constitutional discussions has once again highlighted Canadians' desire and need to know their history. But which history? In the opinion of some historians, Canadianists have done a disservice to their compatriots by forsaking national political history in favour of increasingly specialized research into areas such as women's history, regional history, working class history and ethnic history. This call for a renewed emphasis on national political history raises the central issue of how to produce a history that accurately represents the experience of the diverse elements which constitute the Canadian community. An examination of some selected themes from women's history suggests that a reconceptualization of political history and its relationship to social history would result in a more integrated and meaningful approach to our collective past.